Age-related macular degeneration therapy: a review. Issue 3 (May 2020) - Ammar, Michael J.; Hsu, Jason; Chiang, Allen; Ho, Allen C.; Regillo, Carl D.
Abstract : Purpose of review: The purpose of this review is to describe the current clinical landscape of potential future therapies for both nonexudative (dry) and exudative (wet) age-related macular degeneration (AMD). We highlight some of the more promising treatments that are furthest along in development. Recent findings: Patients with dry AMD have long been hoping for a highly efficacious treatment that may slow disease progression or even help regain vision. Patients with wet AMD have many effective treatment options but still there are those who have suboptimal responses or are burdened by the high frequency of treatment. We detail exciting new concepts and targets for novel medications. Specifically, for dry AMD we discuss research looking at complement inhibition, neuroprotection, visual cycle modulators, cell-based therapies, and anti-inflammatory agents. For wet AMD we summarize new, potentially more durable anti-vascular endothelial growth factor agents, extended release options, and gene therapy. Summary: There are promising new strategies for AMD. Many of the potential new treatments are in or have recently completed phase 2 or phase 3 clinical trials with promising results thus far, including some that have received US Food and Drug Administration approval. Additional therapeutic breakthroughs will likely continue to occur thanks to the number of clinical trials that are nearing the finish line.